Non-invasive measurement of steroids in fish-holding water: Important considerations when applying the procedure to behaviour studies - Scott, Alexander P. (2012)
Fish behaviourists are increasingly turning to non-invasive measurement of steroid hormones in holding water, as opposed to blood plasma. When some of us met at a workshop in Faro, Portugal, in September, 2007, we realised that there were still many issues concerning the application of this procedure that needed resolution, including: Why do we measure release rates rather than just concentrations of steroids in the water? How does one interpret steroid release rates when dealing with fish of different sizes? What are the merits of measuring conjugated as well as free steroids in water? In the ‘static’ sampling procedure, where fish are placed in a separate container for a short period of time, does this affect steroid release— and, if so, how can it be minimised? After exposing a fish to a behavioural stimulus, when is the optimal time to sample? What is the minimum amount of validation when applying the procedure to a new species? The purpose of this review is to attempt to answer these questions and, in doing so, to emphasize that application of the non-invasive procedure requires more planning and validation than conventional plasma sampling. However, we consider that the rewards justify the extra effort.